Import Substitution Elasticity in Antidumping Measures: A Case Study of Pakistani Firms Behaviour - Aaamir Hussain Siddiqui; Nazish Kiran; Mirza Aqeel Baig (International Journal of Experiential Learning & Case Studies, 2024)
This study explore the factors which influencing the firms to file Anti-Dumping cases in Pakistan with the special focus on Import Substitution elasticity as major factor. The study employs Probit regression approach to estimate the potential factors which induce the firms to approach the authority to impose the anti-dumping measures to counter the unfair trade practice and shelter the domestic industry. The potential factors are, Elasticity of substitution, Real Effective Exchange Rate, Industry competitiveness, Trade liberalization, quality legal system, GDP and total domestic production of commodities against which anti-dumping duty is imposed. The estimation result shows that higher level of elasticity of substitution, Industrial competitiveness level, real effective exchange rate and trade openness would increase the probability of imposing anti-dumping duty. While quality of Legal system, GDP and Higher production level would induce a lesser probability of imposition of anti-dumping duty. This study help to understand the behavior of the local business entities asking for shelter against the import competing products and unfair trade practice like dumping etc.        There are very limited studies on the relationship between import substitution elasticity and anti-dumping measure. For developing countries, like Pakistan, this is kind of pioneer study which result are contrary to Developed countries.